Western Architectural Aesthetics’ Impact on Purchase Intent, Satisfaction, and Recommendations in Indonesia - Basmantra, Ida Nyoman; Wijaya, Rayhan; Mimaki, Caren Angellina (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Tourism growth in Indonesia has driven the rapid emergence of restaurants and cafes adopting Western architectural styles, causing a shift in consumer lifestyles, expectations, and overall dining experiences. This study aims to examine the effect of Western-style architectural design on Indonesian consumers' willingness to purchase, satisfaction, and willingness to recommend. Referring to the Stimulus-Organism-Response (S-O-R) Model and the Theory of Planned Behavior, this study positions perceived quality as a mediating variable, with social media marketing and accessibility as moderating variables. Data collection was conducted through a survey of 454 consumers spread across several major provinces in Indonesia. Data analysis used partial least squares structural equation modeling (PLS-SEM) to examine the relationships between variables in the research model. The results show that Western-style architectural design has a significant influence on Indonesian consumers' responses, both directly and through the mediation of perceived quality. Although social media marketing was not proven to have a moderating effect, accessibility showed a negative moderating effect on the relationship between perceived quality and consumer behavior, including satisfaction, purchase intention, and recommendations. These findings confirm that architectural elements are not merely aesthetic aspects, but also strategic elements in shaping consumer perceptions and decisions. Theoretically, this research enriches understanding of the role of design in consumer behavior, while practically providing insights for hospitality and service industry players in designing spaces that are not only visually appealing but also support overall service quality